Understanding the molecular interaction of BSA protein with antibiotic sulfa molecule(s) for novel drug development - Mavani, A.; Ray, Debes; Aswal, Vinod K.; Bhattacharyya, Jhimli (Journal of molecular structure, 2023)
•The binding interaction and thermodynamic aspects into binding of sulfa (SN) molecules (sulfadiazine and sulfamethazine) towards plasma protein (bovine serum albumin; BSA) were elucidated via biophysical tools.•The results were complemented through light scattering and computational analyses.•Overall molecular mechanism; binding characteristics, charges and structural analyses reveal the spontaneity of the interaction (coupled with negative enthalpy & positive entropy changes) with structural perturbation of the giant protein moiety upon ligation.•Electrostatic and hydrophobic forces govern the association process with major contributions from non-poly-electrolytic forces.•Molecular docking data show the binding of SN at Pocket-I of the active site of BSA. Sulfonamide/ sulfa drug (SN) are extensively studied due to their potential antibiotic property. The study of the interaction of bio-macromolecules and small molecules has been a subject of significant interest with varied applications in drug development and modification. The present study aimed to determine the structure, binding characteristics and thermodynamic aspects into binding of sulfamolecules (sulfadiazine and sulfamethazine) towards plasma protein - bovine serum albumin (BSA). The spectrofluorometric titrations study indicates that SN is bound non-cooperatively to BSA protein with the binding affinities and the binding stoichiometry (n) to be in the order of 104 M-1and 1:1 respectively. The quenching constants were observed to decrease with increase in temperature, indicating static quenching mechanism. The negative molar Gibbs energy suggested the spontaneity of the interaction process. The negative enthalpy and positive entropy change(s) indicated towards the involvement of both electrostatic and hydrophobic forces during association process. Salt dependent fluorescence study revealed major contributions from non-poly-electrolytic and less poly-electrolytic forces. Thermal denaturation, circular dichroism (CD), synchronous fluorescence, small angle neutron scattering (SANS) and zeta (ζ)-potential result indicates minor structural change of BSA upon association with sulfa drug. Molecular docking (MD) study further supports the experimental results and shows the ligand binding at Pocket-I of the active site of BSA. The results obtained thus advance our insights into drug-protein interaction patterns which provide help and guidance to biomedical and pharmaceutical researchers for the rational designing of drugs and for the development of more effective and targeted therapies. [Display omitted]